Home improvement. The complete second season [videorecording (DVD)] - Finestra, Carmen; McFadzean, David; Williams, Matt, 1964- (ABC Studios, 2015)
Tim Taylor has his own household project-themed cable TV show, but that does little to earn him respect from his wife and children.